Paraclinus sini Hubbs 1952 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Paraclinus sini Hubbs, 1952. Flapscale Blenny. To 6 cm (2.4 in) TL (Allen and Robertson 1994). Laguna Ojo de Liebre, central Baja California into northern Gulf of California (Rosenblatt and Parr 1969). Benthic; depth: intertidal to 15 m (50 ft) (Rosenblatt and Parr 1969). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 199, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...